Drastic-based methodology for assessing groundwater vulnerability in the gümüşhacıköy and merzifon basin (amasya, turkey) (2013)
In recent years, preparation of aquifer vulnerability maps has become crucial in order to prevent adding new ones to those aquifers that have been contaminated due to environmental effects and been out of use. When preparing vulnerability maps for the basin in which the Gümüşhacıköy and Merzifon aquifers are located, GIS techniques and DRASTIC method are used. In the basin which contains two sub-provinces and is characterized by intensive agricultural activities, groundwater flow is approximately directed toward the west-east and there exist numerous villages across the aquifer.  In order to prepare vulnerability map, DRASTIC layers were created using parameters such as groundwater level, recharge, aquifer environment, topography and hydraulic conductivity. The aquifer vulnerability map was prepared by overlapping the layers by means of GIS.  In the Gümüşhacıköy basin, three different vulnerability zones were determined according to DRASTIC scores; low ( and lt;100), medium (100-140) and high ( and gt;140).  Based on the vulnerability map, it is found that the Gümüşhacıköy Basin has a low contamination potential.  It is established that %16 of the Basin displays high vulnerability and %47 displays low vulnerability. Areas with high vulnerability generally overlap with those areas where slope is low and soil media above the aquifer is permeable.